Improvement of working posture in the metal casting industry to prevent musculoskeletal disorders - Afiqoh Akmalia Fahmi; Arinda Soraya Putri; Rizal Dwiyanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
Less ergonomic work postures such as bending and squatting have the potential to pose work risks. When muscles receive static loads repeatedly and for a long time, it causes complaints of damage to joints, ligaments, and tendons commonly referred to as musculoskeletal disorders (MSDs) or injuries to the musculoskeletal system. This study aimed to determine the level of risk of work postures performed by workers in each work activity using the Rapid Entire Body Assessment (REBA) and Ovako Working Posture Analysis System (OWAS) methods and provide suggestions for improving work postures to minimise the occurrence of work risks. The research was conducted at the foundry of metal in the Casting section. Initial data in the form of Nordic Body Map (NBM) questionnaire data used to determine complaints in the musculoskeletal system and data in the form of image documentation on each work activity used as material for analysing the assessment of the REBA and OWAS methods. Proposals for improving the working posture were given in the form of adding foundations for moulding and pattern-making activities, the design of tools for metal liquid pouring activities, and furnace designs for metal smelting. Proposals for improving the working posture were given in the form of adding foundations for moulding and pattern making, the design of tools for metal liquid pouring, and furnace designs for metal smelting.